1989
DOI: 10.1111/j.1365-2265.1989.tb01253.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Growth Hormone Binding Protein Activity in Healthy Neonates, Children and Young Adults: Correlation With Age, Height and Weight

Abstract: Serum growth hormone binding protein (GHBP) activity was estimated in healthy neonates (n = 6), children and adolescents (n = 97) and young adults (n = 19). GHBP activity was measured by incubating 125I-hGH (human growth hormone) (approximately 25,000 c.p.m.) with serum (100 microliters) in the presence and in the absence of excess unlabelled hGH, followed by separation of specifically bound 125I-hGHBP complexes from free 125I-hGH by gel filtration on Ultrogel AcA44 minicolumns. The results are expressed as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
54
1

Year Published

1992
1992
1999
1999

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(62 citation statements)
references
References 20 publications
7
54
1
Order By: Relevance
“…A positive correlation between serum GHBP pretreatment levels and BMI was found in this study as in others (19)(20)(21)(22), suggesting that nutritional factors affect BMI and GHBP in parallel. As expected, IGF-I levels increased significantly during the first 3 mo of hGH treatment, and they remained constant thereafter.…”
Section: Discussionsupporting
confidence: 64%
“…A positive correlation between serum GHBP pretreatment levels and BMI was found in this study as in others (19)(20)(21)(22), suggesting that nutritional factors affect BMI and GHBP in parallel. As expected, IGF-I levels increased significantly during the first 3 mo of hGH treatment, and they remained constant thereafter.…”
Section: Discussionsupporting
confidence: 64%
“…In the prepubertal period, the response of endogenous GH to pharmacological stimuli often becomes evident only after priming with sex hormones (10)(11)(12). During puberty the secretion of both GH and IGF-I increases (13,14). Kamp et al (15) in a recent review of available data concluded that GH treatment of prepubertal short children results in a somewhat faster rate of progression in boys and an earlier onset of puberty in girls.…”
Section: Discussionmentioning
confidence: 99%
“…In the human fetus, in spite of very high levels of circulating GH (13,14), only low levels of tissue GH receptors (15,16) and of serum GH-BP (17)(18)(19) have been reported. The physiologic significance of these findings remains unclear.…”
mentioning
confidence: 99%